Production of negative-emission biomethane by twin double-bed pressure swing adsorption with tail gas sequestration - Golmakani, Ayub; Nabavi, Seyed Ali; Manovic, Vasilije (Elsevier, 2020)
Selective removal of CO2 during biogas upgrading and subsequent sequestration can transform the produced biomethane from a carbon-neutral to carbon-negative energy source. Such technology can be considered as bioenergy with carbon capture and storage (BECCS), i.e., as a negative-emission technology (NET). In this research, porous polymeric beads (PPBs) with a practical working capacity above atmospheric pressure and cyclic performance were developed to be used for biogas upgrading by pressure swing adsorption (PSA) without the need for vacuum. The CO2 and CH4 equilibrium isotherms of PPBs were measured in the temperature range of 0–70 °C and in the pressure range of 0–10 bar. The dynamic breakthrough curves of 40:60 (vol%) CO2/CH4 gas mixture were measured at 2 bar and 10 bar. These isotherms and breakthrough curves were used as inputs in a dynamic PSA simulation model to predict the performance of a twin double-bed PSA biogas upgrading process. The model indicated that biomethane with 91% CH4 recovery can be produced and a stream of >90% CO2 purity from the tail gas, suitable for geological storage, can be separated. It should be highlighted that unlike current state-of-the-art PSA units, the proposed process using PPBs can upgrade biogas with minimal energy consumption for regeneration of adsorbents. The proposed selective tail gas separation scheme can be used to produce carbon-negative biomethane.
Keywords: Biogas upgrading; Pressure swing adsorption; PSA; Biomethane; Carbon sequestration; Negative-emission technologies